Association between Height of Interproximal Papilla and Different Clinical Parameters - Tanvir, Syed Adil; Sharjeel, Muhammad; Ahmed, Yasir Ikram; Ali khan, Asma Wahid; Fatima, Natasha; Abbas, Aliza (Pakistan Armed Forces Medical Journal, 2026)
Objective: To assess interdental cleaning habits, demographic factors, and clinical parameters, and analyze their association with the height of the interproximal papilla over a defined study period.Study Design: Analytical cross-sectional study.Place and Duration of Study: Armed Forces Institute of Dentistry (AFID) Rawalpindi, Pakistan, from Apr to Sep 2024.Methodology: A total of 29 subjects were selected for examining 202 interproximal papillae of the anterior maxillary region. Norland and Tarnow classification system was used for clinically classifying the interproximal papillae, with score range 0 to 3. By using periodontal probe transparency through the marginal gingiva, the periodontal phenotype was evaluated. Along with this, height of contact point and height of the papilla was also measured.Results: Age positively correlated with papilla scores but negatively with papilla height (p